1998
DOI: 10.1002/hep.510270222
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localization of endothelin-1 and increased production in liver injury in the rat: Potential for autocrine and paracrine effects on stellate cells

Abstract: Endothelin (ET) peptides have been implicated in the pathogenesis of several biological processes within the liver. ET levels are elevated in the circulation of patients with cirrhosis, and recent data suggest that ET may be overproduced in the liver itself in this condition. The aims of the current study were to elucidate the cellular source and expression of endothelin-1 (ET-1) in normal and injured liver, and to investigate its biological effects on stellate cells, the primary target of ETs in the liver. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
166
0
9

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 229 publications
(179 citation statements)
references
References 41 publications
4
166
0
9
Order By: Relevance
“…One possible explanation would be that HSC were not accessible to optimal doses of STI571 in vivo. Another possibility is that the induction of HSC proliferation in liver injury depends upon additional growth factors such as endothelin-1, insulin-like growth factor 1, and transforming growth factor ␣, which stimulate the proliferation of HSC in early culture (Bachem et al, 1993;Rockey et al, 1998).…”
Section: Kinnman Et Almentioning
confidence: 99%
“…One possible explanation would be that HSC were not accessible to optimal doses of STI571 in vivo. Another possibility is that the induction of HSC proliferation in liver injury depends upon additional growth factors such as endothelin-1, insulin-like growth factor 1, and transforming growth factor ␣, which stimulate the proliferation of HSC in early culture (Bachem et al, 1993;Rockey et al, 1998).…”
Section: Kinnman Et Almentioning
confidence: 99%
“…22 In cirrhosis, the total amount of ETs produced was greater in SECs than in hepatic stellate cells, although the relative increase in ET-1 expression was higher in hepatic stellate cells than in SECs. 23 In liver injury, fibrogenesis occurs after activation of hepatic stellate cells, and the activation cascade includes features of proliferation, fibrogenesis, up-regulation of smooth muscle actin, and enhanced contractility. 24 However, the effects of ETs on SECs has not yet been characterized.…”
Section: Discussionmentioning
confidence: 99%
“…18 Recently, Pinzani et al 42 have found that activated stellate cells in human cirrhotic liver are the major site of ET-1 production but that bile duct cells can also produce ET-1. Rockey et al 43 report that ET-1 is synthesized by sinusoidal endothelial cells and stellate cells in rat livers with bile-duct ligation. In the study by Eakes et al, 44 intraportal infusion of endotoxin increased ET-1 mRNA mainly in endothelial cells of normal rat liver.…”
Section: Discussionmentioning
confidence: 99%